AN ANALYSIS OF CONTENT VALIDITY ON SUMMATIVE TEST FOR THE 12th GRADE STUDENTS - Esti Puspitasari (Ma'soem University, 2022)
Content validity is one important thing in evaluating test items. However, based on preliminary observation, the fact, some teachers did not consider the aspect of validity in the summative test, especially content validity. Hence, this study aims to analyze content validity on summative tests in the twelfth grade at public senior high school. The data were collected through document analysis and interviews. The result revealed that the summative test was administrated in the twelfth grade at senior high school has reached poor content validity. This finding hopefully helps the teacher to know how to design the summative better. It is recommended that further studies are conducted with lots of participants and larger classes.